Impacts of vinasse and methods of sugarcane harvesting on the availability of K and carbon stock of an Argisol - Claudinei Alberto Cardin; Carlos Henrique dos Santos; Marcos Antonio Escarmínio (Revista Ceres, 2016)
ABSTRACT Soils of tropical regions are more weathered and in need of conservation managements to maintain and improve the quality of its components. The objective of this study was to evaluate the availability of K, the organic matter content and the stock of total carbon of an Argisol after vinasse application and manual and mechanized harvesting of burnt and raw sugarcane, in western São Paulo.The data collection was done in the 2012/2013 harvest, in a bioenergy company in Presidente Prudente/SP. The research was arranged out following a split-plot scheme in a 5x5 factorial design, characterized by four management systems: without vinasse application and harvest without burning; with vinasse application and harvest without burning; with vinasse application and harvest after burning; without vinasse application and harvest after burning; plus native forest, and five soil sampling depths (0-10 10-20, 20-30, 30-40, 40-50 cm), with four replications. In each treatment, the K content in the soil and accumulated in the remaining dry biomass in the area, the levels of organic matter, organic carbon and soil carbon stock were determined. The mean values were compared by Tukey test. The vinasse application associated with the harvest without burning increased the K content in soil layers up to 40 cm deep. The managements without vinasse application and manual harvest after burning, and without vinasse application with mechanical harvesting without burning did not increase the levels of organic matter, organic carbon and stock of total soil organic carbon, while the vinasse application and harvest after burning and without burning increased the levels of these attributes in the depth of 0-10 cm.